基于层次分析—模糊评价的云计算安全评估与对策 - Ai-min YANG; Fang GAO; Min-hua BIAN; Shu-lei YANG (Tongxin xuebao)
With the rapid development of information technology,cloud computing has become a hot topic.More and more companies and individuals will be their computing needs and storage needs to be delivered to the cloud,so the security problem of cloud computing can not be ignored.First,the security requirements of the four key technologies,such as multi tenant,node communication,remote storage and virtualization in the cloud computing environment were analyzed,the necessity of the construction of cloud computing security was expounded.Then,according to the security requirements of cloud computing,fuzzy comprehensive evaluation model based on ana-lytic hierarchy process was established,and taking a cloud service platform as an example to evaluate its security,get the security level of the service platform is ＆quot;good＆quot;.Finally,according to the security requirements of cloud computing environment and the results of model evaluation,some suggestions in in virtualization security,applica-tion security and data security was put forward,in order to strengthen the cloud computing security,some direction was provided.